Facile and versatile solid state surface modification of silk fibroin membranes using click chemistry. Issue 48 (27th November 2018) - Raynal, Laetitia; Allardyce, Benjamin J.; Wang, Xungai; Dilley, Rodney J.; Rajkhowa, Rangam; Henderson, Luke C.
Abstract : Reported is a fast and versatile protocol to surface modify pre-cast silk membranes targeting tyrosine residues. Abstract : Reported is a fast and versatile protocol to surface modify pre-cast silk membranes targeting tyrosine residues. Enriched alkyne silk membranes were prepared using this method and azides possessing a range of functional groups were tethered to the membrane surface using click chemistry to give a range of water contact angles from 85 ± 3° to 34 ± 6°.